Fabrication of low reflective nanopore-type black Si layer using one-step Ni-assisted chemical etching for Si solar cell application. (14th March 2018) - Takaloo, AshkanVakilipour; Kolahdouz, Mohammadreza; Poursafar, Jafar; Es, Firat; Turan, Rasit; Ki-Joo, Seung
Abstract: Nanotextured Si fabricated through metal-assisted chemical etching (MACE) technique exhibits a promising potential for producing antireflective layer for photovoltaic (PV) application. In this study, a novel single-step nickel (Ni) assisted etching technique was applied to produce an antireflective, nonporous Si (black Si) in an aqueous solution containing hydrofluoric acid (HF), hydrogen peroxide (H2 O2 ) and NiSO4 at 40 °C. Field emission scanning electron microscope was used to characterize different morphologies of the textured Si. Optical reflection measurements of samples were carried out to compare the reflectivity of different morphologies. Results indicated that vertical as well as horizontal pores with nanosized diameters were bored in the Si wafer after 1 h treatment in the etching solution containing different molar ratios of H2 O2 to HF. Increasing H2 O2 concentration in electrochemical etching solution had a considerable influence on the morphology due to higher injection of positive charges from Ni atoms onto the Si surface. Optimized concentration of H2 O2 led to formation of an antireflective layer with 2.1% reflectance of incident light.